Triglyceride Glucose Index and the Risk of Diabetic Nephropathy in Patients with Type 2 Diabetes: A Meta-Analysis - Deng, Sheng; Peng, Ling (Hormone and Metabolic Research, 2024)
Diabetic nephropathy (DN) is a leading cause of end-stage renal disease in patients with type 2 diabetes mellitus (T2DM). This meta-analysis aims to evaluate the association between the triglyceride glucose (TyG) index, a novel marker reflecting insulin resistance, and the risk of developing DN in patients with T2DM. We conducted a comprehensive literature search in PubMed, Embase, and Web of Science databases up to May 12, 2024. Studies assessing the TyG index in relation to DN risk among T2DM patients were included. The pooled relative risks (RRs) with 95% confidence intervals (CIs) were calculated using a random-effects model. A total of eight longitudinal follow-up studies encompassing 15 889 patients with T2DM were included. The pooled analysis revealed a significant association between a higher TyG index and an increased risk of DN in patients with T2DM (RR=1.53, 95% CI: 1.37–1.71, p<0.001; I2=35%). The results of meta-regression analysis suggested that the cutoff of TyG index was positively associated with the RR for the association between TyG index and DN. Subgroup analyses demonstrated that the association was stronger in studies with cutoff of TyG index ≥9.5 as compared to those with the cutoff <9.5 (RR: 1.73 vs. 1.40, p for subgroup difference <0.05). The association was not significantly affected by study design, mean age of the patients, proportion of men, or follow-up durations. In conclusion, higher TyG index is significantly associated with an increased risk of DN in patients with T2DM.
Keywords: triglyceride glucose index; diabetic nephropathy; type 2 diabetes; meta-analysis; insulin resistance